2020
DOI: 10.1002/eat.23318
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on eating disorder risk and symptoms

Abstract: The current COVID-19 pandemic has created a global context likely to increase eating disorder (ED) risk and symptoms, decrease factors that protect against EDs, and exacerbate barriers to care. Three pathways exist by which this pandemic may exacerbate ED risk. One, the disruptions to daily routines and constraints to outdoor activities may increase weight and shape concerns, and negatively impact eating, exercise, and sleeping patterns, which may in turn increase ED risk and symptoms.Relatedly, the pandemic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
392
6
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(487 citation statements)
references
References 41 publications
21
392
6
23
Order By: Relevance
“…These results align with previously published literature (Cohen et al 2017;Holland and Tiggemann 2016;Sherlock and Wagstaff 2019). Taking into consideration the lockdown's associated changes in SNS use stated above, these results might have signi cant implications, as they might indicate that the detrimental effects of SNS could have been exacerbated during the pandemic, and COVID-19 might be linked to increased drive for thinness and risk for eating disorder behaviors relative to media effects, as suggested by Rodgers et al (2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results align with previously published literature (Cohen et al 2017;Holland and Tiggemann 2016;Sherlock and Wagstaff 2019). Taking into consideration the lockdown's associated changes in SNS use stated above, these results might have signi cant implications, as they might indicate that the detrimental effects of SNS could have been exacerbated during the pandemic, and COVID-19 might be linked to increased drive for thinness and risk for eating disorder behaviors relative to media effects, as suggested by Rodgers et al (2020).…”
Section: Discussionsupporting
confidence: 89%
“…Cao et al 2020;Liang et al 2020;Rajkumar 2020). Furthermore, it has been suggested that the pandemic could also have a signi cant impact on eating disorder risk and symptoms (Rodgers et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The present ndings suggest that psychological conditions-speci cally, DEB symptoms-of children and adolescents with T1D were not aggravated by lockdown conditions. This contradicts the general assumption that "social distancing" and isolation-creating anxiety, sadness, anger, and perception/sense of loneliness-may have a negative psychological impact [1] and even exacerbate eating disorder risks [44], further compromising individuals with psychopathological and eating problems [27,28,45,46]. Furthermore, recent evidence from Italian samples [47][48][49][50][51] describe youths with T1D as suffering from DEBs more frequently than healthy peers.…”
Section: Discussionmentioning
confidence: 96%
“…The increased risk of ED behavior related to media effects can also be caused by the COVID-19 pandemic. Media plays a role in three ways: (1) specific exposure to harmful eating and appearances related to media, especially social media; (2) Effects of media use in general; (3) Increased use of video conferencing while working at home (Rodgers et al, 2020). The restrictive diet that increased during the COVID-19 pandemic may occur due to the fear of leaving home to buy food or getting rid of certain foods that are feared to be contaminated.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic can lead to the development of eating disorders (ED) behaviors in some people and exacerbate existing pathologies in others, where ED behaviors tends to be exacerbated by the pandemic through multiple pathways, especially in vulnerable groups including those with body image and also eating concerns (Rodgers et al, 2020). In vulnerable individuals, concerns about health and fitness during quarantine may be a precipitating factor for the development of ED, while other factors such as increased social media use time as well as the toxic influence of objectification of thin ideal become further risk factors (Fernández-Aranda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%